Applied psychology for social work - Ingleby, Ewan (Transforming social work practice., 2010)
Psychology offers potential explanations for complex aspects of human behaviour and development: for this reason it is now an important part of the social work syllabus. This accessible, practical book enables students to apply psychology to their own practice and considers psychology in the context of social care.